T Cells as an Emerging Target for Chronic Pain Therapy - Laumet, Geoffroy; Ma, Jiacheng; Robison, Alfred J.; Kumari, Susmita; Heijnen, Cobi J.; Kavelaars, Annemieke (Frontiers in Molecular Neuroscience, 2019)
The immune system is critically involved in the development and maintenance of chronic pain. However, T cells, one of the main regulators of the immune response, have only gained interest more recently in investigations on chronic pain pathophysiology. Emerging clinical data suggest that patients with chronic pain have a different phenotypic profile of circulating T cells compared to controls. At the preclinical level, findings on the function of T cells are mixed and differ between nerve injury, chemotherapy, and inflammatory models of persistent pain. Depending of the type of injury, the subset of T cells and the sex of the animal, T cells may contribute to the onset and/or the resolution of pain, underlining T cells as a major player in the transition from acute to chronic pain. Specific T cell subsets release mediators such as cytokines and endogenous opioid peptides that can promote or suppress, or even resolve pain. Inhibiting the pain promoting functions of T cells and/or enhancing the beneficial effects of pro-resolution T cells may offer new disease-modifying strategies for the treatment of chronic pain, which is highly needed in view of the current opioid crisis.